Web Development with MongoDB and NodeJS : - Satheesh, Mithun (Birmingham, 2009)
Chapter 1: Welcome to JavaScript in the Full Stack; Chapter 2: Getting Up and Running; Chapter 3: Node and MongoDB Basics; Chapter 4: Introducing Express; Chapter 5: Templating with Handlebars; Chapter 6: Controllers and View Models; Chapter 7: Persisting Data with MongoDB; Chapter 8: Creating a RESTful API; Chapter 9: Testing Your Code; Chapter 10: Deploying with Cloud-Based Services; Chapter 11: Single-Page Applications with Popular; Chapter 12: Popular Node.js Web Frameworks